Bromophenol blue discoloration using peroxidase immobilized on highly activated corncob powder - Galárraga, Julio César Vinueza [UNESP]; Santos, Andréa Francisco dos [UNESP]; Bassan, Juliana Cristina [UNESP]; Goulart, Antônio José [UNESP]; Monti, Rubens [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of the present study was to evaluate the efficacy of peroxidase immobilized on corncob powder for the discoloration of dye. Peroxidase was extracted from soybean seed coat, followed by amination of the surface of the tertiary structure. The aminated peroxidase was immobilized on highly activated corncob powder and employed for the discoloration of bromophenol blue. Amination was performed with 10 or 50 mmol.L-1carbodiimide and 1 mol.L-1ethylenediamine. The amount of protein in the extract was 0.235 ± 0.011 mg.mL-1and specific peroxidase activity was 86.06 ± 1.52 µmol min-1.mg-1, using 1 mmol.L-1ABTS as substrate. Ten mmol.L-1and 50 mmol.L-1 aminated peroxidase retained 88 and 100% of the initial activity. Following covalent immobilization on a corncob powder-glyoxyl support, 10 and 50 mmol.L-1aminated peroxidase retained 74 and 86% of activity, respectively. Derivatives were used for the discoloration of 0.02 mmol.L-1bromophenol blue solution. After 30 min, 93 and 89% discoloration was achieved with the 10 mmol.L-1and 50 mmol.L-1derivatives, respectively. Moreover, these derivatives retained 60% of the catalytic properties when used three times. Peroxidase extracted from soybean seed coat immobilized on a low-cost corncob powder support exhibited improved thermal stability. Keywords: Peroxidases. Multipoint immobilization of enzymes. Aminated enzymes. Corncob powder. RESUMO Descoloração de azul de bromofenol utilizando peroxidase imobilizada em pó de sabugo de milho altamente ativado Nesta pesquisa a enzima peroxidase foi extraída do tegumento de sementes de soja, e a superfície da estrutura terciária foi aminada. A peroxidase aminada foi imobilizada em suporte pó de sabugo de milho altamente ativado e utilizado na descoloração de azul de bromofenol. A aminação da peroxidase foi realizada com carbodiimida em concentrações de 10 e 50 mmol.L-1, e 1 mol.L-1de etilenodiamina. A quantidade de proteínas no extrato foi de 0,235 ± 0,011 mg.mL-1, e a atividade específica da peroxidase foi 86,06 ± 1,52 µmol min-1.mg-1, usando 1 mmol.L-1de ABTS como substrato. A peroxidase aminada a 10 mmol.L-1reteve 88% e a aminada a 50 mmol.L-1reteve 100% da atividade inicial. As peroxidases aminadas a 10 ou 50 mmol.L-1foram covalentemente imobilizadas em suporte glioxil-pó de sabugo de milho com atividade recuperada de 74% e 86%, respectivamente. Os derivados obtidos foram utilizados na descoloração de solução de azul de bromofenol 0,02 mmol.L-1. Após 30 min 93% de descoloração foram alcançados com o derivado glioxil-pó de sabugo de milho com a peroxidase aminada 10 mmol.L-1e 89% com a aminada 50 mmol.L-1. Estes derivados mantiveram 60% das propriedades catalíticas, quando utilizado por três vezes. A peroxidase extraída do tegumento da semente de soja imobilizada em suporte de baixo custo pó de sabugo de milho apresentou melhoria na estabilidade térmica da enzima. Palavras-chave: Peroxidases. Imobilização multipontual de enzimas. Aminação de enzimas. Pó de sabugo de milho.
Keywords: eroxidases, imobilização multipontual de enzimas, aminação de enzimas; pó de sabugo de milho